Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan di PT Tri Adi Bersama (Anteraja) Cabang Tebet. - Putri, Dea Belani; Rosmita (CV Warnak Johanna Nusantara, 2026)
Human resources are important assets in achieving organizational goals. This study aims to analyze the influence of the work environment and job satisfaction on employee work productivity at PT Tri Adi Bersama (Anteraja) Tebet Branch. A quantitative approach was used with a total sample technique involving 35 employees as respondents. There were several tests carried out, namely data quality tests, classical assumption tests, hypothesis tests and determinant coefficient tests. The tool used to process the data in this study was SPSS software version 27. In the Work Environment variable (X1), the calculated t value was 1.728 with a significance level of 0.094> 0.05. This calculated t value was smaller than the t table, which was 2.034. This means that the Work Environment has no effect and is not significant on Work Productivity. In the Job Satisfaction variable (X2), the calculated t value was 2.984 with a significance level of 0.005 <0.05. This calculated t value was greater than the t table, which was 2.034. This indicates that H0 is rejected and Ha is accepted. This means that the Job Satisfaction variable has a significant effect on Work Productivity. From the F test results, the calculated F value is 30.867 > F table 3.295, and sig 0.000. With a confidence level (α) of 5%. Then Ha is accepted and H0 is rejected. So the Work Environment (X1) and Job Satisfaction (X2) variables together (simultaneously) have an effect on Work Productivity (Y). This finding emphasizes the importance of creating a conducive work environment and increasing job satisfaction to support optimal employee performance in the logistics sector. Keywords: Work Environment, Job Satisfaction, Employee Productivity